THE UTILIZATION OF INTERNATIONAL FINANCIAL REPORTING STANDARDS WITHIN THE FRAMEWORK OF UPDATING REGIONAL DEVELOPMENT STRATEGIES - Boiko , O. S.; Matskiv , O. I.; Kostyrko , D. R.; Klop , V. M. (The actual problems of regional economy development, 2024)
The authors of this article explore the integration of International Financial Reporting Standards (IFRS) into regional development strategies with the primary aim of understanding its implications for economic growth. It seeks to research how the adoption of IFRS influences various facets such as transparency, investor confidence, and economic development within regions, employing a rigorous qualitative research approach. This research reveals outcomes of IFRS adoption on regional development strategies and economic growth. The authors found that Canada's swift adoption of the standards correlated with a 15% increase in foreign investment. Conversely, Argentina's slower adoption resulted in a modest 5% increase. In Europe, integration of the standards led to a 20% improvement in market efficiency. China and India's strides saw a 25% surge in capital market capitalization. South Africa's leadership in adoption translated into a 10% increase in SME capital access and a 7% GDP growth. These findings underscore IFRS's pivotal role in driving regional economic stability and growth, emphasizing the need for alignment with development objectives. Unlike many previous studies that have predominantly focused on quantitative analyses, this research solely employs qualitative research methods. The practical significance of this research extends to its implications for policymakers, government agencies, and regulatory bodies. By providing qualitative insights into how these stakeholders can better align IFRS implementation with regional development objectives, the research offers actionable guidance for promoting economic growth and stability within regions. This practical orientation underscores the relevance and applicability of the research findings in real-world decision-making contexts, making it a valuable resource for stakeholders involved in regional development planning and policy formulation. Overall, this article represents a contribution on IFRS adoption and regional development, offer novel insights that enrich understanding of this complex relationship.